Deforestation and forest loss in Condorcanqui Province, Amazonas, Peru, during the period 2001-2021 - Vicuña Yonz, Jose Angelo (2023)
The article analyzes deforestation and forest loss in the Condorcanqui Province, Amazonas, during the 2001 to 2020 time period. It is observed that year 2020 experienced the highest deforestation rate, indicating a significant increase compared to previous years. This large-scale deforestation can have serious environmental consequences, such as, biodiversity loss and increased greenhouse gas emissions. On the other hand, year 2009 shows the lowest deforestation rate, indicating a decrease in forest loss compared to the previous year. However, a negative rate does not necessarily imply a net increase in forest coverage, as it can reflect regeneration or compensation processes in previously affected areas. Illegal logging is identified as one of the main causes of deforestation, and the responsibility of state institutions to control and combat this activity, promoting sustainable forest resource management, is highlighted. In conclusion, there was a concerning increase in deforestation in the Condorcanqui Province, Amazonas, during the studied period. It is necessary to take effective measures to put a stop to illegal logging, promote conservation practices and sustainable use of forest resources, strengthen oversight and monitoring of forest activities, and encourage the participation of local communities in forest management.